2023
DOI: 10.1021/jacs.3c04725
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Conformational Regulations in Ground and Excited States for Realizing Stimulus-Responsive and Wide-Tuning Room-Temperature Phosphorescence

Abstract: Understanding the changes of molecular conformations is crucial for realizing multiple emissive triplet states in room-temperature phosphorescence (RTP) materials. In this work, we report two molecules, 4,4′-dimethylbenzil (DMBZ) and 4,4′-di-tert-butylbenzil (DBBZ) with conformation-dependent luminescence, and demonstrate that stimulus-responsive and wide-tuning RTP emissions can be realized via synergetic conformational regulations in ground and excited states. Due to conformational changes, DMBZ and DBBZ sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Phosphorescence color tuning is a hot topic in the field of UORTP. Generally, phosphorescence properties (including color, lifetime, and quantum yield) should closely depend on the molecular structure of the Phosphorescence Unit , molecular structures of phosphorescence molecules (such as the donor–acceptor structure) constructed with the Phosphorescence Unit , and intermolecular interactions between the Phosphorescence Unit and matrix. Bd and BCz-1 give out (photoactivated) orange ultralong phosphorescence , in a PMMA film at room temperature; BCz, N-1 and N-2 ,, all emit (photoactivated) green ultralong phosphorescence in a PMMA film at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorescence color tuning is a hot topic in the field of UORTP. Generally, phosphorescence properties (including color, lifetime, and quantum yield) should closely depend on the molecular structure of the Phosphorescence Unit , molecular structures of phosphorescence molecules (such as the donor–acceptor structure) constructed with the Phosphorescence Unit , and intermolecular interactions between the Phosphorescence Unit and matrix. Bd and BCz-1 give out (photoactivated) orange ultralong phosphorescence , in a PMMA film at room temperature; BCz, N-1 and N-2 ,, all emit (photoactivated) green ultralong phosphorescence in a PMMA film at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In the dilute MCH solution of ( S )‐ 1 ( c =20 μM, 298 K), atomic force microscopy (AFM) revealed the formation of helical nanofibers with a height of 2.7 nm (Figure 1a and Figure S2). The S 1 0→0 and S 1 0→1 transitions [11c] of the carbonyl units in the UV/Vis spectrum were observed at 342 and 327 nm, respectively (Figure 1b). The relative intensity of S 1 0→0 /S 1 0→1 vibronic bands was 0.48 at 298 K, significantly lower than that at 343 K (1.01, Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Quite recently, the utilization of external stimuli (such as excitation wavelength, force and temperature) has been an effective way to obtain color-tunable afterglow materials, which have attracted increasing attention due to their irreplaceable advantages in anti-counterfeiting applications. 20–25 Up to now, research on multi-color afterglow has achieved some success, and even obtained efficient and long-lived color-tunable RTP in rare materials. 26–31 For example, Huang et al reported a series of full-color RTP elastomers by modifying the chemical structure of monomers; 26 Tao et al achieved full-color RTP in polymer-based materials by doping a series of polycyclic aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%